Building Better Conservation Organisations with Blockchain Technology - Rand Kwong Yew Low; Gopalasamy Reuben Clements (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
Blockchain technology can enable non-profit organisations (NPOs) to create a large, diverse, and engaged community of donors and stakeholders in an autonomous and transparent manner [...]